Case Report: Azathioprine-induced Sweet’s syndrome with associated myocardial infarction - Commins, Natalie; Subhaharan, Deloshaan; White, Lauren (Frontiers in Medicine, 2025)
Sweet’s syndrome (SS) is an acute febrile neutrophilic dermatosis characterized by a rash with tender erythematous plaques or nodules, fevers and leukocytosis. Drug-induced SS is a subtype of SS which is associated with a growing number of medications including azathioprine (AZA). Cardiovascular complications secondary to SS are rare but have been described in case reports and include myocardial infarction and myopericarditis. We report a man in his 60’s with left-sided colonic inflammatory bowel disease (IBD) and perianal disease who developed SS 3 weeks post commencement of AZA. His admission was complicated by an inferolateral ST elevation myocardial infarction occurring concurrently with SS. Clinical improvement occurred with AZA cessation and introduction of intravenous steroids.